Tolerance, Ngajeni and Nrimo as Javanese Value to Reduce Bullying Behavior - Yunita Dwi Setyaningsih; Chr. Argo Widiharto; Sunan Baedowi; Lina Putriyanti (Bisma The Journal of Counseling, 2026)
Bullying remains a serious problem that can hinder the development of students' potential and trigger long-term psychological impacts, such as social disintegration, negative self-evaluation, and depression. This study seeks to examine the impact of Javanese behavior on bullying conduct among students. The study used a quantitative approach with a survey design involving 943 Javanese high school and vocational high school students (429 males; 514 females). Data were collected through a Google Form-based Javanese behavior and bullying behavior questionnaire. Data analysis was conducted using simple linear regression analysis to test the relationship between variables. The results showed a significant regression model (F = 17.274; p < 0.05), indicating that Javanese behavior influences bullying. Of the 14 respondent cities, four cities showed a significant influence: Surakarta, Purbalingga, Banjarnegara, and Kebumen. The dimensions of tolerance, ngajeni, and giving in are related to physical, verbal, and psychological bullying. This study confirms that internalization of Javanese cultural values has the potential to be a preventive strategy for bullying and can be integrated into guidance and counseling services to strengthen character and harmony.